Balancing on the brink: Lebanon, tangled up in the Syrian war, struggles to maintain its stability - Heiko Wimmen (Stiftung Wissenschaft und Politik (SWP), 2015)
So far, the Syrian war and the involvement of Lebanese actors in it has not spread to Lebanon, despite the fears of many. In spite of irreconcilable differences on the Syrian issue, Lebanon's political camps have reached a fragile consensus that makes it possible for political institutions to function at least rudimentarily and for the security situation to be provisionally stabilized. However, this consensus remains precarious and threatened by the ambitions of Lebanese actors and by regional tensions. Moreover, Hezbollah's active involvement in the Syria conflict steadily increases the likelihood of a renewed military confrontation with Israel. Germany and its European partners must do their part to pre-empt such a confrontation, to support the dialogue between the Lebanese parties through mediation, and to stop regional tensions from spilling over. (SWP Comments)
Keywords: 320